Pretrauma Center Red Blood Cell Transfusion Is Associated With Reduced Mortality and Coagulopathy in Severely Injured Patients With Blunt Trauma. Issue 5 (May 2015) - Brown, Joshua B.; Cohen, Mitchell J.; Minei, Joseph P.; Maier, Ronald V.; West, Michaela A.; Billiar, Timothy R.; Peitzman, Andrew B.; Moore, Ernest E.; Cuschieri, Joseph; Sperry, Jason L.
<x xml:space="preserve">Abstract</x> Objective: To evaluate the association of pretrauma center (PTC) red blood cell (RBC) transfusion with outcomes in severely injured patients. Background: Hemorrhage remains a major driver of mortality. Little evidence exists supporting PTC interventions to mitigate this. Methods: Blunt injured patients in shock arriving at a trauma center within 2 hours of injury were included from the Glue Grant database. Subjects were dichotomized by PTC RBC transfusion. Outcomes included 24-hour mortality, 30-day mortality, and trauma-induced coagulopathy [(TIC), admission international normalized ratio >1.5]. Cox regression and logistic regression determined the association of PTC RBC transfusion with outcomes. To address baseline differences, propensity score matching was used. Results: Of 1415 subjects, 50 received PTC RBC transfusion. Demographics and injury severity score were similar. The PTC RBC group received 1.3 units of RBCs (median), and 52% were scene transports. PTC RBC transfusion was associated with a 95% reduction in odds of 24-hour mortality [odds ratio (OR) = 0.05; 95% confidence interval (CI), 0.01–0.48; P < 0.01], 64% reduction in the risk of 30-day mortality [hazard ratio = 0.36; 95% CI, 0.15–0.83; P = 0.02], and 88% reduction in odds of TIC (OR = 0.12; 95% CI, 0.02–0.79; P = 0.03). The matched cohort included 113 subjects (31% PTC RBC group). Baseline characteristics were similar. PTC RBC transfusion was associated with a 98% reduction in odds of 24-hour mortality (OR = 0.02; 95% CI, 0.01–0.69; P = 0.04), 88% reduction in the risk of 30-day mortality (hazard ratio = 0.12; 95% CI, 0.03–0.61; P = 0.01), and 99% reduction in odds of TIC (OR = 0.01; 95% CI, 0.01–0.95; P = 0.05). Conclusions: PTC RBC administration was associated with a lower risk of 24-hour mortality, 30-day mortality, and TIC in severely injured patients with blunt trauma, warranting further prospective study.